Pengaruh Media Trainer terhadap Hasil Belajar Praktek Instalasi Listrik Komersil Mahasiswa Pendidikan Teknik Elektro - Ricky Nelson Tampubolon; Sukarman Purba; Farhan Syahputra; Meisias Veronika Br Sembiring (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
Electrical installation learning is the process of understanding how to install, maintain, and repair electrical systems. This includes an understanding of basic electrical principles, safety codes and standards, and best practices in the installation and maintenance of electrical equipment. This study aims to evaluate the effect of using media trainers in practical learning of commercial electrical. Installations on the learning outcomes of electrical engineering education students. The research method used was a quasi-experiment with a nonequivalent design. The samples for this research were two groups of students, each consisting of 10 people. One group received learning using trainer media, while the control group received conventional learning. Learning outcome data is collected through a final test which includes cognitive, affective and psychomotor aspects. The results of data analysis show that the use of media trainers significantly improves student learning outcomes in all aspects measured compared to conventional learning. The implication of these findings is the importance of using technology in supporting practical learning in the context of electrical engineering education.